An Analysis of Students’ Difficulties in Writing Recount Text - Ariani, Egiesta Dwi (Jurnal Simki Pedagogia, 2023)
Teaching English in Junior High School focuses on improving four language skills namely listening, speaking, reading, and writing. The students are expected to be able to master those four language skills. Improving productive skills is the most important in teaching English. One of the productive skills that have to be improved is writing. However, in practical level, a lot of students have difficulties in writing English texts. Therefore, this research aims to analyze students’ difficulties in writing recount text at the 8th students SMP 15 Kota Serang. The method used in this research was qualitative method which used some instruments like documents, questionnaires, and interview. Based on the result of the research, the most difficult aspects of writing recount encountered by the students were in term of grammar, and then followed by the use of verb, capitalization, the use of to be, punctuation, spelling, preposition, and vocabulary. Moreover, based on the result of students’ recount tasks, the biggest errors made by the students were error of misformation, and then followed by error of omission, error of misorder, and error of addition.